2020
DOI: 10.20473/jn.v15i1sp.18995
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review: The Experience of Patient with Diabetic Foot Ulcers

Abstract: Introduction: Diabetic foot ulcers can have an impact on the individual responses related to the disease process and healing. The response depends on the perception of the disease, its severity, the environmental factors and the level of family support. The response that often occurs is the existence of fear and anxiety which is due to the stress experienced by the individual. The purpose of this study was to explore the experience of patients with diabetic foot ulcers.Methods: This study used the Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Often patients with DM who have diabetic foot ulcers require amputation of that part of the body and bear medical costs five times higher than patients without foot ulcers (Federation International Diabetes., 2019 ;Elkashif, Mahdy and Elgazzar, 2021;Thotad, Bharamagoudar and Anami, 2023). Patients with DFU will experience limited life and require strong efforts to adapt to their conditions (Alfaqih, Kusnanto and Padoli, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Often patients with DM who have diabetic foot ulcers require amputation of that part of the body and bear medical costs five times higher than patients without foot ulcers (Federation International Diabetes., 2019 ;Elkashif, Mahdy and Elgazzar, 2021;Thotad, Bharamagoudar and Anami, 2023). Patients with DFU will experience limited life and require strong efforts to adapt to their conditions (Alfaqih, Kusnanto and Padoli, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study has reported that DFUs contribute to the heavy burden of managing care, causing significant loss of ambulatory function, economic stress (due to medical care costs), job losses, and emotional upheaval (Crocker et al, 2021). Treatment of DFUs is not a simple question of alleviating physical problems; it is also influenced by patientsʼ perception and experience of problems (Alfaqih et al, 2020;Coffey et al, 2019). Understanding patients' QOL is important to achieving successful treatment of DFUs.…”
Section: Introductionmentioning
confidence: 99%
“…They also have financial burdens, feel helpless, blame themselves and feel there is uncertainty in their lives. [23][24][25] Examination of the ulceration based on the depth, edge, shape and size to determine the severity of the ulcer and the treatment that the patient will receive. 26 Obesity itself, as well as hypertriglyceridemia, can directly increase the risk of developing peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%